DE-INDUSTRIALIZATION OR POST-INDUSTRIALIZATION: THE PROBLEMS OF TYPOLOGY OF UKRAINIAN REGIONS - Корнус, Анатолій (Human Geography Journal, 2014)
The paper examines the structure of employment by economic activity in the context of the administrative-territorial units of Ukraine. Found that the processes of de-industrialization are most significant impact on the employment structure. Based on the analysis of the ratio between employed in the primary (agriculture, forestry and fisheries), secondary (mining and manufacturing industries and construction) and tertiary (service industries) sectors the typology of Ukrainian regions was performed with the release of the nine types of regional macro-structures of employment.